PKMS Pelatihan Usaha dan Pemasaran Produk UKM Keripik Tempe ’86’ - Muhammad Tahwin (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The program of stimulus community partnership aims to expand the market share and develop the human resources quality for the partner, it is the UKM of Keripik Tempe ‘86”, Tahunan Village, Sale District, Rembang Regency. The activities carried out including training, facilitating and accompanying. Training is carried out in two stages. The first training stage includes the material such as, business management, financial administration, business motivation, product packaging, product photograph techniques, and product innovation. The second training stage includes the material such as, e-commerce, making data base and sales transaction. Facilitation program is carried out by facilitating web creation. Activity for expanding market share is carried out by PKMS team with the purpose that the partner is able to manage web in order to expand the market share, also able to carry out financial administration well. The result of the activity shows that: (1) There is an enhancement of partnership managerial capability from business management or financial administration, (2) Partner is able to manage e-commerce media to input product data, and sales transaction, (3) Partner has capability to carry out online selling transaction.